Oil Extraction from Trichosanthes tricuspidata Seed using Conventional Soxhlet Apparatus - Jayakumar, C.; Devi, V. Mansa; Reddy Prasad, D.M.; Sridar, R. (Asian Journal of Chemistry, 2019)
Soxhlet set up is used for the extraction of bio-oil from the seeds of Trichosanthes tricuspidata using various solvents (methanol, hexane, isopropyl alcohol). In the present study, the oil from solvent extraction method is investigated for the presence of fatty acid groups and also tested for suitability of this oil being used as a cheap source for producing bio-oil. The bio-oil extraction is influenced by various factors like time of extraction, types of solvent used for extraction and the production rate is also predominately influenced by the particle size of the sample (seed) for extraction. The analysis of the constituents in bio-oil produced is done through a GC-MS and the functional group is determined by FT-IR. This work is carried out in a lab scale and hence the extraction process is initiated with the particle size ranging from 1 mm, 0.55 mm and 3 mm with a variable time period of extraction such as 1, 2, 3 and 7 h. Particle size of 3 mm was selected in order to study the effect of solvent type. The experimental results have indicated the optimal condition for the highest yield of oil extraction of 20 % (w/w). The optimum values of extraction time and particle size are 180 min and 0.55 mm, respectively and also the experimental results have revealed isopropyl alcohol as the suitable extraction solvent.